Temperate urban wetland plankton community stability driven by environmental variables, biodiversity, and resource use efficiency: A case of Hulanhe Wetland - Tao, Tao; Wang, Hao; Na, Xinyuan; Liu, Yan; Zhang, Nannan; Lu, Xinxin; Fan, Yawen (Frontiers in Ecology and Evolution, 2023)
In this study, we explored the driving factors behind plankton community structure. Due to the rapid development of cities, the occupation and development of wetland resources have increased lately, making the urban wetland ecosystems unstable and degrading the ecological functions gradually. Understanding the driving factors behind plankton community structure has certain theoretical and guiding significance for the protection, sustainable development, and ecological restoration of aquatic biodiversity in urban wetland ecosystems. We set up 12 sampling points in the Hulanhe Wetland, with the continuous monitoring of plankton from April to August and October 2021. The eco-environmental factors, plankton community structure, biodiversity index, resource use efficiency (RUE), and Bray–Curtis community turnover value were analysed. A total of 209 species of 91 genera, 42 families, 11 classes, 22 orders of phytoplankton, and 90 species of four classes of zooplankton were identified. The community structure was mainly composed of Bacillariophyta, Chlorophyta, Cyanophyta, Protozoa, and Rotifera. To explore the correlation between phytoplankton and zooplankton, a correlation study was performed. We found a stable feeding preference between phytoplankton and zooplankton. The key influencing factors were identified by ordinary least squares regression, and the main driving factors of plankton community structure were discussed. The results showed that the stability of the Increased biodiversity and resource utilization efficiency have led to more stable plankton communities. This stability pattern is also strongly affected by water temperature, pH and total nitrogen in the external environment. This study will be helpful in the restoration of damaged wetlands, which would be beneficial for the protection of urban wetland ecosystems.